Reconstructing the Values of the Islamization of the Archipelago as a Foundation for Strengthening Religious Moderation in Islamic Religious Education - Nur Azizatul Haqiah; Dwi Ratnasari (Rumah Moderasi Beragama of UIN Siber Syekh Nurjati Cirebon, 2026)
Purpose ̶ This study examines the educational values embedded in the Islamization of the Indonesian Archipelago and their relevance to strengthening religious moderation in Islamic Religious Education (IRE). Design/methods/approach ̶ This study employs a qualitative library research approach using qualitative content analysis of primary literature published between 2021 and 2026, complemented by authoritative reference books on the Islamization of the Archipelago. Findings ̶ The findings identify six dominant values embedded in the Islamization of the Archipelago: tasamuh (tolerance), tawassuth (moderation), tawazun (balance), I’tidal (justice), persuasive da’wah, and respect for local culture. Conclusion ̶ These values are conceptually aligned with the principles of religious moderation and can be reconstructed into learning objectives, instructional materials, teaching strategies, and school culture within Islamic Religious Education. Research Implication ̶ This study contributes a conceptual reconstruction model that bridges the historical values of the Islamization of the Archipelago with contemporary Islamic Religious Education, providing a historically grounded and culturally relevant framework for strengthening religious moderation.